(untitled) (El-Wahat Journal for Research and Studies, 2020)
This Study Deals With The Study Of The Reformer-Cant In The Region Of « Oued Mzab » During The Period From 1920 To 1970. To This End, Singing Is One Of The Most Effective Tools For Diffusing And Saving Ideas. Topics, Events And Opportunities In This Area. We Based In This Study On A Typed Notebook That Contains Many Of These Songs In Addition To The Oral Tales Of The Elements That Were Belonging Or Simultaneous To The Singing Groups, As Well As To Other Manuscripts That Return To The Study Phase. This Study Is Therefore An Attempt To Representing And Recording The Songs That Take Place In This Region Which Has Had A Real Reforming And Scientific Activity. Key Words- Reformist Singing , Oued Mizeb, Algiers, Reformist Movement